The assessment of electromagnetic field radiation exposure for mobile phone users - Buckus, Raimondas; Strukcinskiene, Birute; Raistenskis, Juozas (Vojnosanitetski pregled, 2014)
Background/Aim. During recent years, the widespread use of mobile phones has resulted in increased human exposure to electromagnetic field radiation and to health risks. Increased usage of mobile phones at the close proximity raises questions and doubts in safety of mobile phone users. The aim of the study was to assess an electromagnetic field radiation exposure for mobile phone users by measuring electromagnetic field strength in different settings at the distance of 1 to 30 cm from the mobile user. Methods. In this paper, the measurements of electric field strength exposure were conducted on different brand of mobile phones by the call-related factors: urban/rural area, indoor/outdoor setting and moving/stationary mode during calls. The different types of mobile phone were placed facing the field probe at 1 cm, 10 cm, 20 cm and 30 cm distance. Results. The highest electric field strength was recorded for calls made in rural area (indoors) while the lowest electric field strength was recorded for calls made in urban area (outdoors). Calls made from a phone in a moving car gave a similar result like for indoor calls; however, calls made from a phone in a moving car exposed electric field strength two times more than that of calls in a standing (motionless) position. Conclusion. Electromagnetic field radiation depends on mobile phone power class and factors, like urban or rural area, outdoor or indoor, moving or motionless position, and the distance of the mobile phone from the phone user. It is recommended to keep a mobile phone in the safe distance of 10, 20 or 30 cm from the body (especially head) during the calls.